Pengaruh Waktu Pengomposan Media Tanam terhadap Pertumbuhan dan Hasil Jamur Tiram Putih (Pleorotus ostreatus): Influence of Timing of Planting Media on the Growth and Results of White Oyster Mushrooms (Pleorotus ostreatus) - Kusnayadi, Heri; Pratama, Indra Wira; Suhada, Ikhlas; Wijayanti, Nila (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2021)
The cultivation of consumption mushrooms in Indonesia is showing an encouraging development. Currently, Indonesia is included as one of the world’s major mushroom suppliers. Mushrooms are a source of vegetable protein that does not contain cholesterol and can prevent high blood pressure, heart disease, diabetes, and can reduce body weight. The research objective was to determine the effect of composting time on planting media on the growth and yield of white oyster mushrooms. The research was conducted in the Mapin Kebak Village, sub-district Alas Barat star from May to June 2020. The research was conducted using an experimental method and using a completely randomized design consisting of 5 treatments, where each treatment consisted of three replications. The research treatments consisted of M1 = composting for 6 hours; M2 = composting for 12 hours; M3 = composting for 24 hours; M4 = composting for 36 hours and M5 = composting for 48 hours. Furthermore, the data from the observations were analyzed by ANOVA at the real level of 5%. If the results of the data analysis show a significant difference, then a further test is carried out using the Least Significant Difference Test at the 5% real level. The results of the analysis showed that the fastest time to spread mycelium was in the M5 treatment, the composting time was 48 hours. The fastest primordia emergence time was 24 hours composting M3 treatment. The heaviest fruit weight was in treatment M3 and the lowest fruit weight was in treatment M1.